Facade, Port House - Ghosh, Ayan (2023)
Port House (Old Bombay Port Trust building), located on Shoorji Vallabhdas Road, is an imposing building constructed in the first phase of the development of Ballard Estate in the 1890s. However, with ever-increasing maritime traffic, in 1911, it was decided that a new custom house be constructed, which was built adjoining the Port House.